CODE MIXING PHENOMENON IN YOUTUBE VIDEO A CASE STUDY OF PITA’S LIFE ACCOUNT - Rimadhani, Novia Rizky; Arifin, M. Bahri; Setyowati, Ririn (Fakultas Ilmu Budaya Universitas Mulawarman, 2022)
Code mixing as a part of multilingualism is one of interesting topics to be discussed nowadays as it is often encountered by anyone and anywhere in the present time. Code Mixing happens in real life since linguistic study is not limited to literary work only but in real life when the phenomena can be found, and one of them is in Pita’s Life Account YouTube Video. Pita’s Life Account YouTube Video contains Code Mixing of three different languages including English, Indonesian, and Manado’s Language. The focus of this research is to understand the types and reasons of code mixing that found in Pita’s Account YouTube Videos. This research is qualitative research using Code Mixing which aims to identify types and reason of Code Mixing in Pita’s Life Account YouTube Video. The theories in this research are Code Mixing by Holmes (2013), Muysken (2000) and Hockett (1958). The researcher did the research through library research, and descriptive approach while doing observation to collect the data. The result shows that Code mixing analysis on this research is found some data from types of insertion of phrase and words, alternation and congruent lexicalizations. Then the researcher also found some data from the reason of need filling motive and prestige filling motive.